Cutaneous findings in myotonic dystrophyCapsule Summary - Ha Eun Kong, MD, PhD; Brian P. Pollack, MD, PhD (JAAD International, 2022)
Myotonic dystrophy types 1 and 2 are a group of complex genetic disorders resulting from the expansion of (CTG)n nucleotide repeats in the DMPK gene. In addition to the hallmark manifestations of myotonia and skeletal muscle atrophy, myotonic dystrophy also affects a myriad of other organs including the heart, lungs, as well as the skin. The most common cutaneous manifestations of myotonic dystrophy are early male frontal alopecia and adult-onset pilomatricomas. Myotonic dystrophy also increases the risk of developing malignant skin diseases such as basal cell carcinoma and melanoma. To aid in the diagnosis and treatment of myotonic dystrophy related skin conditions, it is important for the dermatologist to become cognizant of the common and rare cutaneous manifestations of this genetic disorder. We performed a PubMed search using the key terms “myotonic dystrophy” AND “cutaneous” OR “skin” OR “dermatologic” AND “manifestation” OR “finding.” The resulting publications were manually reviewed for additional relevant publications, and subsequent additional searches were performed as needed, especially regarding the molecular mechanisms of pathogenesis. In this review, we aim to provide an overview of myotonic dystrophy types 1 and 2 and summarize their cutaneous manifestations as well as potential mechanisms of pathogenesis.